Palatini side of inflationary attractors - Järv, Laur; Racioppi, Antonio; Tenkanen, Tommi (Physical review. D, 2018)
We perform an analysis of models of chaotic inflation where the inflaton field ϕ is coupled nonminimally to gravity via ξϕngμνRμν(Γ),n>0. We focus on the Palatini theory of gravity, i.e., the case where the assumptions of general relativity are relaxed (that of the connection being the Levi-Civita one) and the gravitational degrees of freedom are encoded in not only the metric but also the connection Γ, which is treated as an independent variable. We show that in this case the famous attractor behavior of simple nonminimally coupled models of inflation is lost. Therefore the attractors are not universal, but their existence depends on the underlying theory of gravity in a subtle way. We discuss what this means for chaotic models and their observational consequences.